Factors Related To Open Defecation Free Behavior In Kuala Cenaku Public Health Center, Indragiri Hulu Regency In 2022: Faktor-Faktor Yang Berhubungan Dengan Perilaku Buang Air Besar Sembarangan (BABS) Di Wilayah Kerja Puskesmas Kuala Cenaku Kabupaten Indragiri Hulu Tahun 2022 - Desvita Anzelina; Sri Desfita; Emy Leonita; Nila Puspita Sari; Elmia Kursani (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Community Based Total Sanitation (STBM) is a government program with the aim that people no longer practice open defecation. Based on data taken from the Public Health Sector, the Health Office of Indragiri Hulu Regency in 2020, which has not yet fully implemented Community Based Total Sanitation (STBM), namely Kuala Cenaku 10%. The purpose of this study was to determine the behavior of open defecation in the working area of the Kuala Cenaku Health Center in 2022. This type of research was quantitative with a cross sectional design. The population of this study is the head of the family or wife in the kelurahan Teluk Sungkai , Pulau Jumat, Pulau Gelang, Kuala Cenaku and Tanjung Sari totaling 2,129 families, with a large sample of 96 respondents. The sampling technique used Proportional Random Sampling. Data analysis was carried out univariate and bivariate. The results of the study found that there was a relationship between mileage (p value = 0.00, POR = 39,531), latrine ownership (p value = 0.00, POR = 2128,000), while the knowledge, attitudes and support of community leaders were not related to behavior. Defecation indiscriminately. Respondents who do not have latrines are 2128 times more at risk of open defecation behavior compared to respondents who have latrines. It is suggested to the responsible for environmental health to empower the community and coordinate with the Health Office or across sectors related to the provision of healthy latrines